Application of High- and Low-Pass Spatial Filters in Analysis of Cone Penetration Test (CPTu). Issue 1 (March 2021) - Rainer, J.; Bagińska, I.
Abstract: The paper examines the high and low pass spatial filters used in the Cone Penetration Test (CPT) recordings in the soil and aims to demonstrate their usefulness and effectiveness in the interpretation of CPT measurements. The procedure of low-pass inverse filtration was used to reduce the effects associated with the occurrence of thin layers. High-pass filters were used to find places where the boundary of layers between different Soil Behaviour Type (SBT) could potentially exist. The application of both filters was tested on natural soils and on anthropological dumping soils.